Robustly optimal monetary policy with near-rational expectations - Michael Woodford (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
The paper considers optimal monetary stabilization policy in a forward-looking model, when the central bank recognizes that private-sector expectations need not be precisely modelconsistent, and wishes to choose a policy that will be as good as possible in the case of any beliefs that are close enough to model-consistency. It is found that commitment continues to be important for optimal policy, that the optimal long-run inflation target is unaffected by the degree of potential distortion of beliefs, and that optimal policy is even more historydependent than if rational expectations are assumed.
urn:nbn:de:hebis:30-38229
Keywords: E52; E58; E42; 330; Optimal Monetary Policy; Commitment; History-Dependent Policy; Geldpolitik; Konjunkturpolitik; Rationale Erwartung; Theorie